PENGARUH PRESTASI BELAJAR DAN SELF REGULATED LEARNING TERHADAP TINGKAT STRES SISWA FULL DAY SCHOOL DI SMK KESEHATAN UTAMA INSANI TAHUN 2020 - Bambang Mardisentosa; Ida Faridah; Bella Aprilia Pertiwi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
The Full Day School system has been approved through the Ministry of Education number 23 2017. The implementation of the Full Day School system makes students stressed and stressed, because students are always asked to be active in every subject and homework given so that their rest time is reduced. Objective: To find out the effect of Self Regulated Learning achievement on the stress level of Full Day School students at 2020 Main Health Insani Vocational School. Research Method: In this study using a comparative causal or cross sectional approach using normality test, multicollinearity, heteroscedasticity, multiple regression, T test and F test. The sample technique used was simple random sampling of 70 respondents. Research Results: Based on the T test, learning achievement has no effect on the stress level of full day school students, Self Regulated Learning has an effect on the stress level of full day school students. Based on the research results of the F test of learning achievement and Self Regulated Learning affect the stress level of full day school students with the results of the F table 12.190 with a value of 0.000 Sig. Conclusion: The results of the study there is the effect of Self Regulated Learning on the stress level of full day school students.